BIOLOGYCAL IMUNOMODULATORS IN THE COMPLEX THERAPY OF INFECTIOUS MONONUCLEOSIS IN CHILDREN - A. G. Bokovoy; I. V. Kovalev; L. F. Makkaveeva; O. A. Volodina; A. A. Komarov; A. Yu. Medkova; N. B. Tanina (Детские инфекции (Москва))
80 patients were observed with infectious mononucleosis (IM) from 2 to 12 years. Diagnosis was confirmed by the definition of M- and G-antibodies to EBV, CMV, HHV6, PCR DNA these viruses, bacteriological and blood-tests investigations. 40 patients was given bifidumbacterin forte 45—90 doses a day and cycloferon 8 mg/kg/weight a day(1-st group). The comparison group consisted of 40 patients with IM receiving symptomatic therapy and antibiotics (2-nd group). The observations shoved significant decreasing of length of clinical symptoms IM in the 1-st group with comparison of the 2-nd group. The obtained results allow to recommend bifidumbacterin forte and cycloferon in the complex therapy in children with infectious mononucleosis.